Fe-Ni-BASED ALLOY SHEET AND METHOD FOR MANUFACTURING THE SAME
By precisely controlling the alloy composition and manufacturing process of Fe-Ni alloy sheets, the challenges of maintaining high magnetic properties and reducing production costs are addressed, resulting in enhanced magnetic performance and rust resistance.
Patent Information
- Application Number
- JP2023150989
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-19
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-09-19
AI Technical Summary
Existing Fe-Ni alloys struggle to maintain high magnetic properties such as initial relative permeability, maximum relative permeability, and saturation magnetic flux density while reducing Ni content to lower production costs, leading to compromised magnetic performance and corrosion resistance.
By strictly controlling the alloy composition of Fe-Ni alloys within specific ranges for elements such as C, Si, Mn, P, S, Ni, Cr, Mo, Cu, Al, Ti, Co, W, N, Sn, Mg, Zr, Ca, and O, and applying precise manufacturing processes including oxidation refining, deoxidation, and cold rolling, the Fe-Ni alloy sheet achieves enhanced magnetic properties and reduced yield.
The controlled composition and manufacturing method result in Fe-Ni alloy sheets with excellent initial relative permeability, maximum relative permeability, and saturation magnetic flux density, while also providing improved rust resistance and reduced production costs.
Smart Images

Figure 2025043605000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an Fe—Ni alloy plate and a method for producing the same. [Background technology]
[0002] As specified in JIS C2531 and IEC standards, Fe-Ni based soft magnetic alloys are broadly classified into Permalloy C alloy (Ni: 72-83 mass%), Permalloy B alloy (Ni: 45-50 mass%), Permalloy D alloy (Ni: 35-40 mass%), etc., depending on the Ni content. High-grade Permalloy C alloy has high magnetic permeability and low coercive force, and is therefore used in magnetic components such as magnetic shielding materials and magnetic sensor materials. However, since Permalloy C alloy contains a lot of Ni and is expensive, it has been replaced by the cheaper Permalloy B alloy as a material for magnetic components. In addition, Permalloy B alloy has a high saturation magnetic flux density, and is also used in watch stators, magnetic lens pole pieces, etc.
[0003] In recent years, the demand for soft magnetic materials such as automobile sensors and magnetic shielding materials has been increasing, while the price of Ni has been on the rise, and there is a movement to replace Permalloy B alloys with cheaper Alloy 42 and Permalloy D alloys, which have a lower Ni content. However, with the decrease in Ni content, the decrease in each magnetic property and corrosion resistance is a problem, and there is a strong demand to maintain the high saturation magnetic flux density, which is a characteristic of Permalloy B alloys. In particular, soft magnetic materials having an initial relative permeability of 3,000 or more, a maximum relative permeability of 30,000 or more, and a saturation magnetic flux density of 1.4 T or more are preferably used for automobile sensors and magnetic shielding materials.
[0004] As a method for improving the magnetic properties of permalloy alloys, Patent Document 1 proposes a method for improving the magnetic properties by subjecting a continuous cast slab to homogenization heat treatment to reduce segregation, but Patent Document 1 does not mention saturation magnetic flux density.
[0005] Patent Document 2 proposes a method for improving magnetic properties by restricting the temperature and time of magnetic annealing of rolled Fe-Ni alloy material and the amount of A-based (Mn-S-based) inclusions in the Fe-Ni alloy, thereby promoting the growth of crystal grains. However, this method aims to improve the coercive force, initial relative permeability, and maximum relative permeability of the obtained soft magnetic component material, and does not consider the saturation magnetic flux density. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2002-173745 A [Patent Document 2] JP 2015-196838 A Summary of the Invention [Problem to be solved by the invention]
[0007] In view of the above circumstances, an object of the present invention is to provide an Fe-Ni based alloy that can impart excellent initial relative permeability, good maximum relative permeability and saturation magnetic flux density, and can be produced with reduced yield, and a method for producing the same. [Means for solving the problem]
[0008] As a result of extensive research aimed at solving the above problems, the inventors discovered that by strictly controlling the alloy composition of an Fe-Ni based alloy, it is possible to improve the magnetic properties of the initial relative permeability, the maximum relative permeability, and the saturation magnetic flux density, and further to obtain an Fe-Ni based alloy that can be manufactured with a reduced yield, thereby completing the present invention.
[0009] The gist of the present invention is as follows. [1] Carbon (C): 0.001~0.05% by mass, Silicon (Si): 0.05 to 0.50 mass%, Manganese (Mn): 0.25 to 1.00 mass%, Phosphorus (P): 0.001~0.030% by mass, Sulfur (S): 0.0001~0.0050% by mass, Nickel (Ni): 35.0 to 44.0 mass%, Chromium (Cr): 0.01 to 0.50 mass%, Molybdenum (Mo): 0.005 to 0.10 mass%, Copper (Cu): 0.01~2.00% by mass, Aluminum (Al): 0.0001 to 0.10 mass%, Titanium (Ti): 0.050% by mass or less, Cobalt (Co): 0.01 to 2.00 mass%, Tungsten (W): 0.01 to 0.50 mass%, Nitrogen (N): 0.001~0.05% by mass, Tin (Sn): 0.0001 to 0.05 mass%, Magnesium (Mg): 0.050% by mass or less, Zirconium (Zr): 0.0001 to 0.05 mass%, Calcium (Ca): 0.0020% by mass or less, Oxygen (O): 0.0002 to 0.01% by mass, An Fe-Ni alloy plate, the balance of which is iron (Fe) and unavoidable impurities. [2] The Fe-Ni-based alloy sheet according to [1], containing Cu, Co and W so as to satisfy the following relational formula (A): 1.5≦20[Cu%]+20[Co%]+80[W%]<50.0 …(A) (In formula (A), % represents mass %) [3] The Fe-Ni alloy sheet according to the above [1] or [2], containing Cu, Co, W, Cr, Mo, P and S so as to satisfy the following relational formula (B): 10≦50([Cu%]+[Co%])+100[W%]+200[Cr%]+800[Mo%]-100[P%]-1000[S%] …(B) (In formula (B), % represents mass %) [4] subjecting the molten metal containing the Fe-Ni alloy raw material to oxidation refining in a secondary refining vessel, such as an AOD furnace or a VOD furnace; a step of introducing Al and / or FeSi alloy into the molten metal after oxidation refining, and performing deoxidation and desulfurization treatment so that the Al content in the molten metal is in the range of 0.0001 to 0.10 mass%, the Si content is in the range of 0.05 to 0.50 mass%, the S content is in the range of 0.0001 to 0.0050 mass%, and the O content is in the range of 0.0002 to 0.01 mass%; A step of continuously casting the molten metal after the deoxidization and desulfurization treatment to form a slab; hot rolling and then cold rolling the resulting slab; The method for producing an Fe—Ni alloy sheet according to any one of the above [1] to [3], comprising: Effect of the Invention
[0010] According to the present invention, by strictly controlling the alloy composition of the Fe-Ni alloy, it is possible to provide an Fe-Ni alloy sheet that can be provided with excellent initial relative permeability, good maximum relative permeability and saturation magnetic flux density, and can be manufactured with a reduced yield, and a manufacturing method thereof. [Brief description of the drawings]
[0011]
Figure 1
Figure 2
[0012] The Fe-Ni alloy plate according to the present invention and the manufacturing method thereof will be described below. The Fe-Ni alloy plate according to the present invention has carbon (C): 0.001 to 0.05 mass%, silicon (Si): 0.05 to 0.50 mass%, manganese (Mn): 0.25 to 1.00 mass%, Phosphorus (P): 0.001-0.030 mass%, sulfur (S): 0.0001-0.0050 mass%, nickel (Ni): 35.0-44.0 mass%, chromium (Cr): 0.01-0.50 mass%, molybdenum (Mo): 0.005-0.10 mass%, copper (Cu): 0.01-2.00 mass%, aluminum (Al): 0.0001-0.10 mass%, titanium (Ti): 0.050 mass% or less, cobalt (Co): 0.01- 2.00 mass%, tungsten (W): 0.01 to 0.50 mass%, nitrogen (N): 0.001 to 0.05 mass%, tin (Sn): 0.0001 to 0.05 mass%, magnesium (Mg): 0.050 mass% or less, zirconium (Zr): 0.0001 to 0.05 mass%, calcium (Ca): 0.0020 mass% or less, oxygen (O): 0.0002 to 0.01 mass%, and the balance is iron (Fe) and unavoidable impurities. In this way, by strictly controlling the alloy composition of the Fe-Ni alloy, it is possible to provide an Fe-Ni alloy sheet that can be imparted with excellent initial relative permeability, good maximum relative permeability and saturation magnetic flux density, and can be manufactured with reduced yield. Since the Fe-Ni alloy sheet according to the present invention can impart such excellent magnetic properties, it is suitable for use as a soft magnetic material such as an automobile sensor, a magnetic shielding material, and a watch stator.
[0013] In addition to satisfying the above compositional components, the Fe-Ni alloy plate according to the present invention preferably contains Cu, Co and W so as to satisfy the following formula (A).
[0014] 1.5≦20[Cu%]+20[Co%]+80[W%]<50.0 …(A) (In formula (A), % represents mass %)
[0015] The above formula (A) expresses the influence of the amount of Cu, Co, and W added on the maximum relative magnetic permeability and saturation magnetic flux density of Fe-Ni alloys as a relational equation for Cu and Co, which have atomic radii close to Ni, and W, which has an ionic radius close to Ni. Figure 1 is a graph showing the relationship between the maximum relative magnetic permeability and saturation magnetic flux density measured by the following test method (magnetic property test) and the value of the above formula (A), and Figure 2 is a graph showing the relationship between the saturation magnetic flux density and the value of formula (A) in the region where the value of formula (A) is 5.0 or less. Figure 1 shows that the maximum relative magnetic permeability is lower than 30,000 when the value of formula (A) is 50.0 or more, and Figure 2 shows that the saturation magnetic flux density is lower than 1.4T when the value of formula (A) is less than 1.5. Therefore, by containing Cu, Co and W in the Fe-Ni alloy plate so that the value of formula (A) is within the range of 1.5 or more and less than 50.0, it is possible to obtain an Fe-Ni alloy plate that can impart excellent maximum relative permeability and saturation magnetic flux density.
[0016] <Magnetic property test> Fe-Ni alloys containing approximately 39.3 mass% Ni as a basic component were melted in a 10 kg capacity high-frequency dielectric furnace for testing. During melting, the amounts of Cu, Co, and W added were varied in each alloy, as shown in Table 1 below. The melted alloys were then cast into molds to form steel ingots, which were then hot forged into forged plates with a thickness of 10 mm. The alloys were then annealed and polished to remove surface scale, and cold rolled to a thickness of 0.8 mm. These cold-rolled plates were processed into ring test pieces with a size of φ45 mm × 33 mm based on JIS C2531, and vacuum (≦5.0×10 -3 The wire was magnetically annealed in a 1125°C (1.2 Pa) atmosphere for 2.5 hours at a constant temperature of 1125°C. After that, 50 turns of enameled copper wire specified in JIS C3202 or JIS C3215 were wound on both the primary and secondary sides, and the maximum relative magnetic permeability (μ max ) and saturation magnetic flux density (B 800 ) was measured. The maximum relative magnetic permeability was measured with a reversed magnetic field of 16 A / m, and the saturation magnetic flux density was measured under a magnetic field of 1600 A / m. The results are shown in Table 2. The numerical values of each component in Table 1 represent "mass %."
[0017] [Table 1]
[0018] [Table 2]
[0019] Thus, Cu, Co and W are important elements for obtaining an excellent saturation magnetic flux density, and a saturation magnetic flux density of 1.4 T or more can be obtained by setting the value of formula (A), which is the relational expression of the amounts of Cu, Co and W added, to 1.5 or more. On the other hand, when the value of formula (A) is 50.0 or more, the maximum relative magnetic permeability becomes less than 30,000. Therefore, the value of formula (A) is preferably within a range of 1.5 or more and less than 50.0, more preferably within a range of 1.5 or more and 40.0 or less, and even more preferably within a range of 1.5 or more and 25.0 or less.
[0020] In addition, the Fe-Ni alloy plate according to the present invention preferably contains Cu, Co, W, Cr, Mo, P and S so as to satisfy the above-mentioned compositional components and the following formula (B).
[0021] 10≦50([Cu%]+[Co%])+100[W%]+200[Cr%]+800[Mo%]-100[P%]-1000[S%] …(B) (In formula (B), % represents mass %)
[0022] The Fe-Ni soft magnetic material may rust during the manufacturing process due to changes in temperature, humidity, etc., and there is concern about deterioration of magnetic properties due to rust. Cu, Co, W, Cr, Mo, P, and S are elements that affect rust resistance, and in the present invention, the Fe-Ni alloy plate contains Cu, Co, W, Cr, Mo, P, and S so as to satisfy formula (B), so that an Fe-Ni alloy plate having excellent magnetic properties and rust resistance can be obtained. In this way, since the Fe-Ni alloy plate exhibits rust resistance, it is possible to omit additional steps such as removing rust and handling to prevent rust generation, and as a result, it is possible to prevent a decrease in workability and a decrease in productivity due to an increase in the number of steps. The value of formula (B) is preferably 10 or more, more preferably 15 or more, and even more preferably 20 or more.
[0023] C: 0.001 to 0.05 mass% C contained in the Fe-Ni alloy sheet is an element necessary for maintaining the strength of the alloy. If the C content is less than 0.001% by mass, the effect is not sufficiently obtained. On the other hand, if the C content exceeds 0.05% by mass, it reacts with Cr and Ti contained in the alloy to form carbides, which inhibits the growth of crystal grains and the movement of domain walls, thereby deteriorating the magnetic properties. Therefore, the C content is 0.001 to 0.05% by mass, preferably 0.001 to 0.01% by mass, and more preferably 0.001 to 0.008% by mass.
[0024] Si: 0.05 to 0.50 mass% The Si contained in the Fe-Ni alloy sheet is an effective element for the deoxidation treatment carried out when manufacturing the Fe-Ni alloy sheet. If the Si content is less than 0.05 mass%, the effect is not sufficiently obtained. On the other hand, if the Si content exceeds 0.50 mass%, the ordered lattice of the Fe-Ni alloy is not in an optimal state, and the magnetic properties are deteriorated. Therefore, the Si content is 0.05 to 0.50 mass%, the lower limit of the Si content is preferably 0.10 mass%, and the upper limit of the Si content is preferably 0.25 mass%. That is, the Si content is preferably 0.05 to 0.25 mass%, and more preferably 0.10 to 0.25 mass%.
[0025] Mn: 0.25 to 1.00 mass% Mn contained in the Fe-Ni alloy sheet is an effective element for forming MnS by combining with S, which reduces hot workability, suppressing the deterioration of hot workability caused by S, and improving punchability by forming MnS. If the Mn content is less than 0.25 mass%, the effect cannot be obtained sufficiently. On the other hand, if the Mn content exceeds 1.00 mass%, MnS is formed in excess, which prevents the growth of crystal grains and the movement of domain walls, thereby deteriorating the magnetic properties. Therefore, the Mn content is 0.25 to 1.00 mass%, preferably 0.25 to 0.60 mass%, and more preferably 0.25 to 0.57 mass%.
[0026] P: 0.001 to 0.030 mass% P contained in the Fe-Ni alloy sheet is an effective element for suppressing the segregation of S to the grain boundaries by segregating to the grain boundaries, promoting the dispersed precipitation of MnS, and improving punchability. If the P content is less than 0.001 mass%, the effect cannot be sufficiently obtained. On the other hand, if the P content exceeds 0.030 mass%, P segregates excessively to the grain boundaries, not only deteriorating the hot workability but also reducing the rust resistance. Therefore, the P content is 0.001 to 0.030 mass%, preferably 0.001 to 0.020 mass%, and more preferably 0.001 to 0.019 mass%.
[0027] S: 0.0001 to 0.0050 mass% S contained in the Fe-Ni alloy sheet is an element that is effective in improving punchability by combining with Mn and Mg to form MnS and MgS. If the S content is less than 0.0001% by mass, the effect is not sufficiently obtained. On the other hand, if the S content exceeds 0.0050% by mass, S segregates at grain boundaries to form low melting point compounds, which not only significantly reduces hot workability but also reduces rust resistance. Therefore, the S content is 0.0001 to 0.0050% by mass, and the lower limit of the S content is preferably 0.0003% by mass, more preferably 0.0005% by mass, and the upper limit of the S content is preferably 0.0040% by mass, more preferably 0.0030% by mass. That is, the S content is preferably 0.0003 to 0.0040% by mass, more preferably 0.0005 to 0.0030% by mass.
[0028] Ni: 35.0 to 44.0 mass% Ni contained in the Fe-Ni alloy sheet is an important element for ensuring magnetic properties. If the Ni content is less than 35.0 mass%, the effect cannot be obtained sufficiently. On the other hand, if the Ni content exceeds 44.0 mass%, the surface of the rolled sheet is scratched or edge cracks are generated during hot rolling, resulting in a decrease in yield. Therefore, the Ni content is 35.0 to 44.0 mass%, the lower limit of the Ni content is preferably 35.7 mass%, more preferably 40.5 mass%, and the upper limit of the Ni content is preferably 42.6 mass%, more preferably 41.5 mass%. That is, the Ni content is preferably 35.7 to 42.6 mass%, more preferably 40.5 to 41.5 mass%.
[0029] Cr: 0.01 to 0.50 mass% Cr contained in the Fe-Ni alloy sheet is an effective element for ensuring rust resistance. If the Cr content is less than 0.01% by mass, the effect cannot be obtained sufficiently. On the other hand, if the Cr content exceeds 0.50% by mass, it bonds with C present in the Fe-Ni alloy to form Cr-based carbides, which impede the movement of the domain wall and deteriorate the magnetic properties. Therefore, the Cr content is 0.01 to 0.50% by mass, the lower limit of the Cr content is preferably 0.02% by mass, more preferably 0.03% by mass, and the upper limit of the Cr content is preferably 0.10% by mass, more preferably 0.08% by mass. That is, the Cr content is preferably 0.02 to 0.10% by mass, more preferably 0.03 to 0.08% by mass.
[0030] Mo: 0.005 to 0.10 mass% Mo contained in the Fe-Ni alloy sheet is an effective element for ensuring rust resistance, and is also an important element for controlling the conditions for forming the ordered lattice that affects the crystal magnetic anisotropy and magnetostriction. If the Mo content is less than 0.005 mass%, the effect is not sufficiently obtained. On the other hand, if the Mo content exceeds 0.10 mass%, the saturation magnetic flux density is reduced. Therefore, the Mo content is 0.005 to 0.10 mass%, with the preferred lower limit of the Mo content being 0.01 mass% and the preferred upper limit of the Mo content being 0.05 mass%. That is, the Mo content is preferably 0.01 to 0.05 mass%.
[0031] Cu: 0.01 to 2.00 mass% Cu contained in the Fe-Ni alloy sheet is an important element for ensuring saturation magnetic flux density and rust resistance at the same time. If the Cu content is less than 0.01 mass%, sufficient rust resistance cannot be obtained. On the other hand, if the Cu content exceeds 2.00 mass%, burrs and sagging occur during slitting or punching, leading to deterioration of the product shape. Therefore, the Cu content is 0.01 to 2.00 mass%, preferably 0.01 to 0.50 mass%, and more preferably 0.01 to 0.40 mass%.
[0032] Al: 0.0001 to 0.10 mass% Al contained in the Fe-Ni alloy sheet is an effective element for deoxidation treatment performed when manufacturing the Fe-Ni alloy sheet. If the Al content is less than 0.0001% by mass, the effect is not sufficiently obtained, and the concentration of O in the Fe-Ni alloy is increased, so that the number of oxide-based inclusions increases and the magnetic properties are deteriorated. On the other hand, if the Al content exceeds 0.10% by mass, the power to reduce MgO in the slag becomes too strong, the concentration of Mg in the Fe-Ni alloy increases, and Ni2Mg, an intermetallic compound with a low melting point, is generated, and the hot workability is deteriorated. At the same time, the power to reduce CaO in the slag becomes too strong, so that the concentration of Ca in the steel increases and the magnetic properties are deteriorated. Therefore, the Al content is 0.0001 to 0.10% by mass, preferably 0.0001 to 0.050% by mass, and more preferably 0.0001 to 0.045% by mass.
[0033] Ti: 0.050 mass% or less The Ti contained in the Fe-Ni alloy sheet combines with C and N present in the Fe-Ni alloy to form Ti-based carbides and nitrides. If the Ti content is too high, it will hinder the growth of crystal grains and the movement of domain walls, thereby deteriorating the magnetic properties. On the other hand, Ti forms nitrides, which act as nuclei for MnS, which is effective in improving punchability, and promotes precipitation. Therefore, in consideration of the balance between the magnetic properties and punchability, the Ti content is 0.050 mass% or less, with a preferred lower limit of the Ti content being 0.001 mass% and a preferred upper limit of the Ti content being 0.020 mass%. That is, the Ti content is preferably 0.001 to 0.020 mass%.
[0034] Co: 0.01 to 2.00 mass% Co contained in the Fe-Ni alloy sheet is an important element for ensuring saturation magnetic flux density and rust resistance at the same time. If the Co content is less than 0.01% by mass, sufficient rust resistance cannot be obtained. On the other hand, if the Co content exceeds 2.00% by mass, burrs and sagging occur during slitting or punching, leading to deterioration of the product shape. Therefore, the Co content is 0.01 to 2.00% by mass, preferably 0.01 to 1.00% by mass, and more preferably 0.01 to 0.50% by mass.
[0035] W: 0.01 to 0.50 mass% W contained in the Fe-Ni alloy sheet is an important element for ensuring saturation magnetic flux density and rust resistance at the same time. If the W content is less than 0.01% by mass, sufficient rust resistance cannot be obtained. On the other hand, if the W content exceeds 0.50% by mass, warping occurs during slitting or punching, leading to deterioration of the product shape. Therefore, the W content is 0.01 to 0.50% by mass, preferably 0.01 to 0.10% by mass, and more preferably 0.01 to 0.05% by mass.
[0036] N: 0.001 to 0.05 mass% N contained in the Fe-Ni alloy sheet is an element necessary for ensuring the strength of the Fe-Ni alloy. If the N content is less than 0.001% by mass, the effect cannot be obtained sufficiently. On the other hand, if the N content exceeds 0.05% by mass, when Ti is present in the Fe-Ni alloy, it bonds with Ti to form a nitride, which inhibits the growth of crystal grains and the movement of domain walls, thereby deteriorating the magnetic properties. Therefore, the N content is 0.001 to 0.05% by mass, and the upper limit of the Ni content is preferably 0.01% by mass, more preferably 0.006% by mass. That is, the Ni content is preferably 0.001 to 0.01% by mass, more preferably 0.001 to 0.006% by mass.
[0037] Sn: 0.0001 to 0.05 mass% Sn contained in the Fe-Ni alloy sheet is an element necessary for ensuring plating properties. If the Sn content is less than 0.0001 mass%, the effect cannot be obtained sufficiently. On the other hand, if the Sn content exceeds 0.05 mass%, the hot workability is deteriorated. Therefore, the Sn content is 0.0001 to 0.05 mass%, and the upper limit of the Sn content is preferably 0.01 mass%, more preferably 0.005 mass%. That is, the Sn content is preferably 0.0001 to 0.01 mass%, more preferably 0.0001 to 0.005 mass%.
[0038] Mg: 0.05 mass% or less Mg contained in the Fe-Ni alloy sheet combines with S present in the Fe-Ni alloy to form MgS. If the Mg content is too high, MgS is formed in excess, which inhibits the growth of crystal grains and the movement of domain walls, thereby deteriorating the magnetic properties. However, Mg is mixed in irreversibly due to manufacturing reasons. Therefore, from the viewpoint of magnetic properties, the Mg content is 0.05 mass% or less, preferably 0.01 mass% or less, and more preferably 0.005 mass% or less.
[0039] Zr: 0.0001 to 0.05 mass% Zr contained in the Fe-Ni alloy sheet is an element necessary for ensuring the strength of the Fe-Ni alloy. If the Zr content is less than 0.0001 mass%, the effect is not sufficiently obtained. On the other hand, if the Zr content exceeds 0.05 mass%, the magnetic properties are deteriorated. Therefore, the Zr content is 0.0001 to 0.05 mass%, preferably 0.0001 to 0.01 mass%, and more preferably 0.0001 to 0.008 mass%.
[0040] Ca: 0.0020 mass% or less Ca contained in the Fe-Ni alloy sheet combines with Al present in the Fe-Ni alloy to form Ca-Al oxide inclusions. If the Ca content is too high, Ca-Al oxide inclusions are formed in excess, which impedes the growth of crystal grains and the movement of domain walls, thereby deteriorating the magnetic properties. On the other hand, Ca is an important element for suppressing the SiO2 activity and controlling the O content to reduce the amount of inclusions. Therefore, from the viewpoint of magnetic properties, the Ca content is 0.0020 mass% or less, the preferred lower limit of the Ca content is 0.0001 mass%, and the preferred upper limit of the Ca content is 0.0010 mass%. That is, the Ca content is preferably 0.0001 to 0.0010 mass%.
[0041] O: 0.0002 to 0.01 mass% If the content of O in the Fe-Ni alloy sheet (molten metal) is less than 0.0002% by mass, the CaO in the slag is reduced, increasing the concentration of Ca in the molten metal, forming excessive Ca-Al oxide-based inclusions, which impede the growth of crystal grains and the movement of domain walls, thereby deteriorating the magnetic properties. On the other hand, if the content of O exceeds 0.01% by mass, oxide-based inclusions are formed with other elements, which impede the movement of domain walls, thereby deteriorating the magnetic properties. Therefore, the content of O is 0.0002 to 0.01% by mass, with a preferred lower limit of the content of O being 0.0005% by mass and a preferred upper limit of the content of O being 0.008% by mass. That is, the content of O is preferably 0.0005 to 0.008% by mass.
[0042] In the Fe-Ni alloy sheet according to the present invention, the balance other than the above components is Fe and unavoidable impurities, and Fe is contained as the main component.
[0043] The thickness of the Fe-Ni alloy plate is not particularly limited, but is preferably 0.05 mm or more and 6.00 mm or less, and more preferably 0.08 mm or more and 4.00 mm or less.
[0044] Next, a method for producing an Fe-Ni alloy plate according to the present invention will be described. The method for producing an Fe-Ni alloy plate according to the present invention includes the steps of: (a) subjecting a molten metal containing a raw material of an Fe-Ni alloy to oxidation refining in a secondary refining vessel of either an AOD furnace or a VOD furnace (hereinafter also referred to as "step (a)"); (b) feeding Al and / or FeSi alloy into the molten metal after oxidation refining, and subjecting the molten metal to deoxidation and desulfurization treatment so that the Al content in the molten metal is in the range of 0.0001 to 0.10 mass%, the Si content is in the range of 0.05 to 0.50 mass%, the S content is in the range of 0.0001 to 0.0050 mass%, and the O content is in the range of 0.0002 to 0.01 mass% (hereinafter also referred to as "step (b)"); (c) continuously casting the molten metal after the deoxidation and desulfurization treatment to form a slab (hereinafter also referred to as "step (c)"); and (d) hot rolling the obtained slab and then cold rolling it (hereinafter also referred to as "step (d)").
[0045] Step (a) In step (a), the molten metal containing the raw material of the Fe-Ni alloy is oxidized and refined using a secondary refining vessel, either an AOD (Argon Oxygen Decarburization) furnace or a VOD (Vacuum Oxygen Decarburization) furnace. The molten metal is obtained by melting the raw material of the Fe-Ni alloy in an electric furnace. For example, iron scrap, nickel, ferronickel, etc. can be used as the raw material, and Fe-Ni alloy slab pieces, Fe-Ni scraps, etc. may also be used. The obtained molten metal is decarburized using a secondary refining vessel, either an AOD furnace or a VOD furnace, and it is possible to discharge the oxidizing slag after decarburization, that is, FeO-CaO-SiO2-based slag, which is a slag containing FeO. This slag also contains chromium oxide, tungsten oxide, titanium oxide, and phosphorus oxide, and these oxides can also be discharged outside the system. As a result, in the obtained Fe-Ni alloy plate, the Cr content can be controlled within the above range, and further, the W content and Ti content can be easily controlled within the above range, and the content of P, which is a harmful impurity element, can be reduced to 0.030 mass% or less. In this way, by performing oxidation refining using either an AOD furnace or a VOD furnace as the secondary refining vessel, it becomes possible to discharge the above-mentioned oxidizing slag out of the system. Note that, in the VOD furnace, the ladle is temporarily moved to a slag removal area and the slag is removed with a slag remover, so that the molten metal temperature is easily reduced, and therefore, the use of an AOD furnace is more effective.
[0046] In addition, the step (a) can appropriately control the contents of Cu, Co and W so that the obtained Fe-Ni alloy plate satisfies the above formula (A). That is, the value of the above formula (A) can be easily controlled within a range of 1.5 or more and less than 50.0, preferably within a range of 1.5 or more and 40.0 or less, more preferably within a range of 1.5 or more and 25.0 or less.
[0047] Step (b) In step (b), Al and / or FeSi alloy are added to the molten metal after oxidation refining to perform deoxidation and desulfurization. Even if the above-mentioned oxidizing slag is removed by oxidation refining, about 1 ton of oxidizing slag still remains on the molten metal. Therefore, considering the FeO concentration in the remaining oxidizing slag and the oxygen concentration in the molten metal, an amount of Al and / or FeSi alloy corresponding to the FeO concentration and the oxygen concentration in the molten metal is added to the molten metal to deoxidize and desulfurize the molten metal. In particular, by adding Al and FeSi alloy so that the content of Al contained in the molten metal is adjusted to be within the range of 0.0001 to 0.1 mass% and the content of Si is adjusted to be within the range of 0.05 to 0.5 mass%, deoxidation and desulfurization proceed in the most preferable form, and in the obtained Fe-Ni alloy plate, the content of O can be controlled to be within the range of 0.0002 to 0.01 mass%, the content of S can be controlled to be within the range of 0.0001 to 0.0050 mass%, and other thermodynamically unstable elements can also be controlled within the above-mentioned ranges. The theory is explained below.
[0048] In the refining process including the above-mentioned steps (a) and (b), the obtained slag plays a very important role. The slag to be formed is not particularly limited, but it is preferable to form a CaO-SiO2-Al2O3-MgO-F slag. CaO contained in such slag can be formed by burning limestone to dissociate CO2 and adding quicklime obtained as CaO into the molten metal, and SiO2 can be formed by oxidation after adding the FeSi alloy. CaO plays a particularly important role in the slag, and the CaO concentration in the slag is preferably controlled to 40 to 70 mass%. MgO can be formed by using magnesia-containing bricks such as dolomite bricks, magnesia bricks, and MgO-C bricks as the refractory material of the secondary refining vessel of either the AOD furnace or the VOD furnace, and dissolving MgO in the slag. In addition, since such bricks are expensive, it is preferable to extend the life of the bricks as much as possible to reduce costs, and MgO-containing waste bricks may be used. F can be controlled by adding fluorite to the molten metal. F is an important component, and by ensuring the fluidity of the slag, the following reactions between the slag and the molten metal proceed, allowing the O content to be controlled within the range of 0.0002 to 0.01 mass%, the S content to be controlled within the range of 0.0001 to 0.0050 mass%, and the Ca content to be 0.0020 mass% or less. Therefore, it is preferable to control the F concentration in the slag to 1 to 10 mass%. In the following reactions, the underlined components are those contained in the molten metal, and the components in parentheses are those contained in the slag.
[0049] Si +2 O → (SiO2) (1) 2(CaO)+ Si → (SiO2)+2 Ca (2) Ca + S → (CaS) (3)
[0050] In order to effectively advance the reaction represented by the above formula (1) toward the right side and control the O content within the range of 0.0002 to 0.01 mass%, the SiO2 activity in the slag must be kept at 10 -2 ~10 -3It is necessary to control the S content as low as possible. For this purpose, CaO is effective as described above, and the SiO2 activity can be controlled by adding quicklime to the molten metal. Furthermore, when the reaction represented by the above formula (2) proceeds toward the right side, and then the generated Ca reacts with S in the molten metal to cause the desulfurization reaction represented by the above formula (3), the S content can be controlled within the range of 0.0001 to 0.005 mass%, and once the Ca has migrated into the molten metal, it reacts with S to consume the Ca, making it possible to control the Ca content to 0.0020 mass% or less.
[0051] Also, as shown in the following formula (4), Al can be used for deoxidization. Generally, industrial FeSi alloys contain about 1 mass% Al as an impurity. Therefore, by adding FeSi alloy to the molten metal, it is possible to control the Al content to within the range of 0.0001 to 0.10 mass%. Also, since Al2O3 in the slag may also react with Si in the molten metal, care must be taken. In other words, if the reaction represented by the following formula (5) becomes active, the Al content will exceed 0.10 mass%. In order to control the reaction represented by the following formula (5), it is necessary to increase the Al2O3 activity in the slag by 10 -2 ~10 -3 If the CaO concentration in the slag is controlled to be as low as possible, the Al content can be easily controlled to be within the range of 0.0001 to 0.10 mass%. To achieve this, it is preferable to control the CaO concentration in the slag to cause the reaction represented by the above formula (2) to proceed toward the right side, and to bring the reaction represented by the following formula (5) into equilibrium and stabilize the reaction, as described above.
[0052] 2 Al +3 О → (Al2O3) (4) 2(Al2O3)+3 Si → 3(SiO2)+4 Al (5)
[0053] In order to control the Mg content to 0.050% by mass or less, it is necessary to suppress the reaction represented by the following formula (6) as much as possible. In this case, it is effective to suppress the MgO in the slag as low as possible, but in consideration of the damage to the bricks and the need to add waste bricks, it is preferable to control the MgO concentration in the slag to within the range of 5 to 20% by mass. In addition, in order to suppress the Mg concentration, it is preferable to control the Si concentration in the molten metal to within the above range and the CaO concentration in the slag to within the above range. This makes it possible to control the Mg content to 0.050% by mass or less.
[0054] 2(MgO)+ Si → (SiO2)+2 Mg (6)
[0055] During decarburization, W forms an oxide called WO3, some of which volatilizes and simultaneously migrates into the slag as shown in the reaction of formula (7) below. The W content can be controlled within the range of 0.01 to 0.50 mass% by adjusting the amount of W added in ladle refining, but it is preferable to control the CaO concentration, MgO concentration, and F concentration in the slag within the above ranges, respectively, to bring the reaction represented by formula (7) below into equilibrium and stabilize the reaction.
[0056] W +3 O → (WO3) (7)
[0057] In order to control the Zr content within the range of 0.0001 to 0.05 mass%, the amount of Zr added can be adjusted in the ladle refining process in the same way as W, but Zr is an element that is easily oxidized as shown in the following formula (8). Therefore, it is preferable to maintain the equilibrium relationship of the reaction represented by the following formula (7) and stabilize the reaction by controlling the CaO concentration, MgO concentration, and F concentration in the slag within the above ranges, respectively, and controlling the O content within the range of 0.0002 to 0.01 mass%.
[0058] Zr +2 O → (ZrO2) (8)
[0059] In order to control the Ti content to 0.050 mass% or less, the reaction represented by the following formula (9) is effectively caused to proceed toward the right-hand side. Here, too, by controlling the CaO concentration, MgO concentration, and F concentration in the slag within the above ranges, reducing the TiO2 activity in the slag, and controlling the O content within the range of 0.0002 to 0.01 mass%, the reaction represented by the following formula (9) can be effectively caused to proceed toward the right-hand side, and ultimately the Ti content can be controlled to 0.050 mass% or less.
[0060] Ti +2 O → (TiO2) (9)
[0061] In order to control the N content within the range of 0.001 to 0.05 mass%, the reaction represented by the following formula (10) is effectively advanced toward the right side. Nitrogen is easily mixed from the atmosphere when the raw material is melted in an electric furnace, but by using an AOD furnace or a VOD furnace, the reaction represented by the following formula (10) advances toward the right side during decarburization, and the N content can be controlled within the above range. That is, during oxygen blowing, CO gas is generated by the reactions represented by the following formulas (11) and (12). The CO gas bubbles thus generated can capture the dissolved nitrogen in the molten metal and transfer it in the form of nitrogen gas into the CO gas, and finally, the nitrogen gas can be removed by discharging the CO gas bubbles outside the furnace. However, even if the CO gas is removed outside the system, the thermodynamic equilibrium value of nitrogen does not fall below 0.001 mass%, so it is possible to control the N content within the range of 0.001 to 0.05 mass%.
[0062] 2 N → N2 [gas] (10) O2 [Gas] +2 Fe → 2FeO[Oxygen gas bubble surface] (11) FeO[Oxygen gas bubble surface]+ C → CO[gas]+Fe[liquid] (12)
[0063] Step (c) In step (c), the deoxidized and desulfurized molten metal is continuously cast to form a slab. The conditions for continuous casting are not particularly limited, but the continuous casting can be performed using a vertical continuous casting machine.
[0064] Step (d) In step (d), the obtained slab is hot rolled and then cold rolled. A hot section is produced through the hot rolling process of the slab, and then the obtained hot section is cold rolled to produce a cold rolled sheet. The conditions of hot rolling and cold rolling are not particularly limited, but the hot rolling can be performed with a Steckel rolling mill, and the cold rolling can be performed with a Sendzimir type cold rolling mill. In addition, before the cold rolling process, annealing and pickling may be performed as necessary to remove surface scale. In this way, the Fe-Ni alloy sheet according to the present invention can be produced.
[0065] By performing magnetic annealing on the cold-rolled sheet obtained by cold rolling, magnetic properties are imparted to the Fe-Ni alloy. The conditions for magnetic annealing are not particularly limited, and magnetic annealing can be performed appropriately using a conventionally known method. Through such steps, the initial relative permeability (μ i ) is 3,000 or more, more preferably 3,500 or more, and preferably the maximum relative permeability (μ max ) is 30,000 or more, more preferably 35,000 or more, and preferably the saturation magnetic flux density (B 800 It is possible to realize an Fe-Ni based alloy sheet exhibiting magnetic properties of 1.4 T or more, more preferably 1.45 T or more. EXAMPLES
[0066] Next, examples of the present invention will be described, but the present invention is not limited to these examples as long as they do not depart from the spirit of the present invention.
[0067] <Examples 1 to 40 and Comparative Examples 1 to 10> 60t of raw materials including iron scrap, nickel, ferronickel, etc. were melted in an electric furnace. Then, oxidation refining was performed in an AOD furnace or VOD furnace for decarburization, dechromization, dephosphorization, etc. Here, dolomite bricks, magnesia bricks, MgO-C bricks were lined on the refractory of the secondary refining vessel of the AOD furnace or VOD furnace for each charge according to the operation cycle. Then, the formed oxidizing slag, that is, FeO-containing slag, FeO-CaO-SiO2 slag, was discharged. This slag also contained Cr oxide, W oxide, Ti oxide, and phosphorus oxide, and was discharged as much as possible from the system. Then, the molten metal was deoxidized and desulfurized while adjusting the contents of Al, Si, S, and O contained in the obtained molten metal using Al and / or FeSi alloy. At this time, CaO-SiO2-Al2O3-MgO-F slag was produced. That is, quicklime was added to the molten metal to form CaO, and SiO2 was formed by oxidation after the addition of the FeSi alloy. The MgO source was made from MgO-containing waste bricks, which also served the purpose of preventing brick meltdown. The F source was prepared by adding fluorite to the molten metal to ensure the fluidity of the slag. The molten steel was then received in a ladle, and the temperature was adjusted by ladle refining, while various ingredients were carefully calculated and added to adjust the alloy composition to the chemical composition shown in Tables 3 and 4 below. The slag composition in Table 5 indicates the slag composition at the end of AOD or VOD refining.
[0068] [Table 3]
[0069] [Table 4]
[0070] [Table 5]
[0071] The deoxidized and desulfurized molten metal was then continuously cast into slabs, which were then hot-rolled, annealed, and pickled, and then cold-rolled to produce Fe-Ni alloy sheets with a thickness of 0.8 mm.
[0072] <Magnetic properties> The obtained Fe-Ni alloy plate was processed into a ring test piece of φ45 mm × 33 mm based on JIS C2531, and vacuum (5.0 × 10 -3 After magnetic annealing under the conditions of 1125℃ soaking in an atmosphere of 1.5 Pa or less for 2.5 hours, 50 turns of enameled copper wire specified in JIS C3202 or JIS C3215 were wound on both the primary and secondary sides, and the initial relative permeability (μ i ), maximum relative permeability (μ max ) and saturation magnetic flux density (B 800 ) were measured. The initial relative permeability and maximum relative permeability were measured with a reverse magnetic field of 16 A / m, and the initial relative permeability was set to a value of 0.8 A / m. The saturation magnetic flux density was measured under a magnetic field of 1600 A / m. Based on the measurement results, the magnetic properties were evaluated as excellent (○) when all three of the following criteria for the initial relative permeability, maximum relative permeability, and saturation magnetic flux density were satisfied. Furthermore, when only two of the following criteria for the initial relative permeability, maximum relative permeability, and saturation magnetic flux density were satisfied, the magnetic properties were evaluated as good (△), and when only one item was satisfied or none were satisfied, the magnetic properties were evaluated as poor (×). The results are shown in Table 5. ·Initial relative permeability: 3,000 or more ·Maximum relative permeability: 30,000 or more ·Saturation magnetic flux density: 1.4 (T) or more
[0073] <Rust resistance> To evaluate rust resistance, the cold-rolled sheet obtained above was cut into 40 x 50 mm test pieces, the surfaces of which were wet-polished with #400 waterproof abrasive paper, and an accelerated rust test was performed. The accelerated rust test was performed at a temperature of 70°C and a relative humidity of 100%, and the test pieces were held horizontally for 72 hours in a 1000 ml beaker containing 200 ml of distilled water, without getting wet. The degree of rust was then evaluated using the following three-level rating number (RN) based on JIS G0595. The results are shown in Table 5. 〇: RN is greater than 2.5 △: RN is 2.0 or more and 2.5 or less ×: RN is less than 2.0
[0074] <Overall rating> The above tests were evaluated comprehensively using the following four-level scale. The results are shown in Table 5. ◎: Both magnetic properties and rust resistance are rated as "○". · 〇: Magnetic properties rated "〇" and rust resistance rated "△" ·△: Magnetic properties are rated as "△", or magnetic properties are rated as "〇" and rust resistance is rated as "×" ×: Magnetic properties are rated as "×", or the product has poor yield.
[0075] [Table 6]
[0076] As shown in Tables 3 to 6, in Examples 1 to 30 using Fe-Ni alloy plates satisfying the range of chemical composition defined in the present invention, both the magnetic properties and the rust resistance were evaluated as "○", and the overall evaluation was also "◎".
[0077] In Examples 31 to 34, the obtained Fe-Ni alloy sheets satisfied the range of chemical composition defined in the present invention, and the magnetic properties were evaluated as "○", but the rust resistance was evaluated as "△", and the overall evaluation was "○".
[0078] In Example 35, the obtained Fe-Ni alloy plate satisfied the range of the chemical composition defined in the present invention, but the value of formula (A) was 50.4 and the maximum relative magnetic permeability was less than 30,000, so the magnetic properties were evaluated as "△". On the other hand, the rust resistance was evaluated as "〇", so the overall evaluation was "△".
[0079] In Example 36, the obtained Fe-Ni alloy plate satisfied the range of the chemical composition defined in the present invention, but the value of formula (A) was 1.4 and the saturation magnetic flux density was less than 1.4 T, so the magnetic properties were evaluated as "△". On the other hand, the rust resistance was evaluated as "◯", so the overall evaluation was "△".
[0080] In Example 37, the obtained Fe-Ni alloy plate satisfied the range of the chemical composition defined in the present invention, but the value of formula (A) was 1.3 and the saturation magnetic flux density was less than 1.4 T, so the magnetic properties were evaluated as "△". On the other hand, the rust resistance was evaluated as "〇", so the overall evaluation was "△".
[0081] In Example 38, the obtained Fe-Ni alloy plate satisfied the range of the chemical composition defined in the present invention, but the value of formula (A) was 50.1 and the maximum relative magnetic permeability was less than 30,000, so the magnetic properties were evaluated as "△". On the other hand, the rust resistance was evaluated as "〇", so the overall evaluation was "△".
[0082] In Example 39, the obtained Fe-Ni alloy plate satisfied the range of the chemical composition defined in the present invention, but the value of formula (B) was 9 and RN was less than 2.0, so the rust resistance was evaluated as "x". On the other hand, the magnetic properties were also evaluated as "○", so the overall evaluation was "△".
[0083] In Example 40, the obtained Fe-Ni alloy plate satisfied the range of the chemical composition defined in the present invention, but the value of formula (A) was 1.4, and the saturation magnetic flux density was less than 1.4 T. Furthermore, the value of formula (B) was 0, and the RN was less than 2.0. Therefore, the magnetic properties were evaluated as "△" and the rust resistance was evaluated as "×", so the overall evaluation was "△".
[0084] In Comparative Examples 1 to 3, the obtained Fe-Ni alloy sheets did not satisfy the range of chemical composition defined in the present invention, and the initial relative magnetic permeability was less than 3,000 and the maximum relative magnetic permeability was less than 30,000, so the evaluation of the magnetic properties was "x". Furthermore, the product yield was poor, and one coil of this charge had severe edge cracks and was scrapped. Therefore, the overall evaluation was "x".
[0085] In Comparative Examples 4 and 5, the obtained Fe-Ni alloy sheets did not satisfy the range of chemical composition defined in the present invention, and the initial relative permeability was less than 3,000 and the saturation magnetic flux density was less than 1.4 T, so the magnetic properties were evaluated as "x". Furthermore, the value of formula (B) was low, and the RN was less than 2.0, so the rust resistance was also evaluated as "x", and the overall evaluation was "x".
[0086] In Comparative Example 6, the obtained Fe-Ni alloy plate did not satisfy the range of chemical composition defined in the present invention, and the saturation magnetic flux density was less than 1.4 T, so the magnetic properties were evaluated as "△". Furthermore, the value of formula (B) was 7, and the RN was less than 2.0, so the rust resistance was evaluated as "×". On the other hand, the product yield was poor, and one coil of this charge had severe edge cracks and was scrapped. Therefore, the overall evaluation was "×".
[0087] In Comparative Examples 7 to 9, the obtained Fe-Ni alloy sheets did not satisfy the range of chemical composition defined in the present invention, and the initial relative permeability was less than 3,000 and the saturation magnetic flux density was less than 1.4 T, so the magnetic properties were evaluated as "x". Furthermore, the value of formula (B) was low, and RN was less than 2.0, so the rust resistance was also evaluated as "x", and the overall evaluation was "x".
[0088] In Comparative Example 10, the obtained Fe-Ni alloy plate did not satisfy the range of chemical composition defined in the present invention, and the initial relative magnetic permeability was less than 3,000 and the maximum relative magnetic permeability was less than 30,000, so the evaluation of the magnetic properties was "x". Furthermore, the product yield was poor, and two of the coils in this charge had severe edge cracks and were scrapped. Therefore, the overall evaluation was "x". [Industrial Applicability]
[0089] The Fe-Ni alloy plate according to the present invention can provide excellent initial relative permeability, good maximum relative permeability and saturation magnetic flux density, and can be manufactured with low yield, so that it can be suitably applied as a soft magnetic material for, for example, automobile sensors, magnetic shielding materials, watch stators, etc.
Claims
1. Carbon (C): 0.001 to 0.05% by mass, Silicon (Si): 0.05 to 0.50% by mass, Manganese (Mn): 0.25 to 1.00 mass%, Phosphorus (P): 0.001 to 0.030% by mass, Sulfur (S): 0.0001 to 0.0050% by mass, Nickel (Ni): 35.0 to 44.0% by mass, Chromium (Cr): 0.01 to 0.50 mass% Molybdenum (Mo): 0.005 to 0.10 mass% Copper (Cu): 0.01 to 2.00% by mass, Aluminum (Al): 0.0001 to 0.10 mass%, Titanium (Ti): 0.050% by mass or less, Cobalt (Co): 0.01 to 2.00 mass%, Tungsten (W): 0.01 to 0.50 mass%, Nitrogen (N): 0.001 to 0.05% by mass, Tin (Sn): 0.0001 to 0.05% by mass, Magnesium (Mg): 0.050% by mass or less, Zirconium (Zr): 0.0001 to 0.05 mass%, Calcium (Ca): 0.0020% by mass or less, Oxygen (O): 0.0002 to 0.01 mass%; The balance of the Fe-Ni alloy plate is iron (Fe) and unavoidable impurities.
2. The Fe-Ni alloy plate according to claim 1, containing Cu, Co and W so as to satisfy the following relational formula (A): 1.5≦20[Cu%]+20[Co%]+80[W%]<50.0…(A) (In formula (A), % represents mass %)
3. The Fe-Ni alloy plate according to claim 1 or 2, containing Cu, Co, W, Cr, Mo, P and S so as to satisfy the following relational formula (B). 10≦50([Cu%]+[Co%])+100[W%]+200[Cr%]+800[Mo%]-100[P%]-1000[S%]...(B) (In formula (B), % represents mass %)
4. A step of subjecting a molten metal containing a raw material of an Fe—Ni alloy to oxidation refining in a secondary refining vessel of either an AOD furnace or a VOD furnace; a step of introducing Al and / or FeSi alloy into the molten metal after the oxidation refining, and performing deoxidation and desulfurization treatment so that the Al content in the molten metal is in the range of 0.0001 to 0.10 mass%, the Si content is in the range of 0.05 to 0.50 mass%, the S content is in the range of 0.0001 to 0.0050 mass%, and the O content is in the range of 0.0002 to 0.01 mass%; A step of continuously casting the molten metal after the deoxidization and desulfurization treatment to form a slab; hot rolling and then cold rolling the resulting slab; The method for producing an Fe—Ni alloy plate according to claim 1 or 2, comprising:
5. A step of subjecting a molten metal containing a raw material of an Fe—Ni alloy to oxidation refining in a secondary refining vessel of either an AOD furnace or a VOD furnace; a step of introducing Al and / or FeSi alloy into the molten metal after the oxidation refining, and performing deoxidation and desulfurization treatment so that the Al content in the molten metal is in the range of 0.0001 to 0.10 mass%, the Si content is in the range of 0.05 to 0.50 mass%, the S content is in the range of 0.0001 to 0.0050 mass%, and the O content is in the range of 0.0002 to 0.01 mass%; A step of continuously casting the molten metal after the deoxidization and desulfurization treatment to form a slab; hot rolling and then cold rolling the resulting slab; The method for producing an Fe-Ni alloy plate according to claim 3, comprising:
Citation Information
Patent Citations
Fe-ni based permalloy, its production method and cast slab
JP2002173745A
PRODUCTION METHOD OF Fe-Ni ALLOY MATERIAL, METHOD OF MANUFACTURING SOFT MAGNETIC COMPONENT, Fe-Ni ALLOY AND SOFT MAGNETIC COMPONENT MATERIAL
JP2015196838A